Digital transformation in aviation industry operations : innovations and sustainable solutions - Dutta, Pushan, 1985-; Ricciuti, Martin; Bogrekci, Ismail; Suseelan, Sumeet (Routledge, 2026)
Digital Transformation in Aviation Industry Operations explores the transformative technologies driving a new era in aviation, focusing on solutions that streamline operations, enhance passenger experience, promote safety, and support sustainable practices. This book provides a comprehensive look at how digital tools are reshaping the airline industry.Focusing on emerging technologies, this textbook offers the most up-to-date treatment of the ways digital innovations are transforming the aviation industry. Covering aspects from communications and weather forecasting to fuel and energy considerations, the book gives readers invaluable insights into how aviation continues to evolve as new technologies are applied.Aimed at postgraduate students and researchers in aviation and operations management, Digital Transformation in Aviation Industry Operations showcases how digital technology can leverage better profitability, sustainability, and improved efficiencies in the aviation industry. It is an essential guide for anyone looking to harness the power of digital transformation in an aviation context.